Menentukan Degree Distribution Optimal Pada Coded Random Access (CRA) Dengan Multi User Detection (MUD) K = 3 Menggunakan Extrinsic Information Transfer (EXIT) Chart - Dio Resya Baaqii; Yusnita Rahayu; Khoirul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This paper proposes an optimal degree distribution for Coded Random Access (CRA) exploiting Multi User Detection (MUD) with capability of K = 3. The CRA with MUD K = 3 can support the fifth telecommunication generation (5G) networks and massive machine-type communications, including the Internet-of-Things (IoT). The optimization is performed by the help of Extrinsic Information Transfer (EXIT) chart, a visual tool describing the behavior of the wireless networks, and a series of computer to validate the expected results. We found that the IoT networks using the proposed optimal degree distribution, having only two terms with less exponent, can achieve the maximum offered traffic (G∗) of 2.736 packet/slot.Keyword: Degree distribution, multi user detection, coded random access.